Community structure and niche breadth of some fish in Pangelang Protected Lake, Kapuas Hulu District - Sri Endah Purnamaningtyas; Dimas Angga Hedianto; Nurfiarini Nurfiarini (Jurnal Iktiologi Indonesia, 2021)
Ecologically, weather changes cause local deviations from regional patterns in waters. So that there will be changes in fish types and food habits.The purpose of this study was to determine changes in fish community structure, food preferences, and area of niches for each type of fish in Pangelang Protected Lake. The research was conducted using a survey method in October 2016 (low tide), June 2018 (transition) and September (flood) 2018. The results obtained: 1. Fish communities in Lake Pangelang obtained a total of 12 families, 30 genera, and 37 species. In the low tide season, there are 21 species of fish caught, 17 species of transition season and 16 types of flood during low tide. 2. In the low tide season, the fish community in Pangelang Lake is dominated by detritivorous fish. In the transitional season, the fish community in Pangelang Lake experiences changes with an increase in the union of phytoplanktivore and insectivore fish. During the flood season, the fish communities in Lake Pangelang underwent a change again where the union of herbivores that used plants increased. Abstrak Secara ekologis, perubahan cuaca menyebabkan penyimpangan lokal dari pola regional pada kondisi perairan sehingga akan terjadi perubahan komposisi jenis ikan dan kebiasaan makanan ikan. Tujuan penelitian ini adalah untuk menganalisis perubahan struktur komunitas ikan, preferensi makanan, dan relung makanan setiap jenis ikan di danau lindung Pangelang. Penelitian dilakukan dengan metode survei pada bulan Oktober 2016 (air surut), Juni 2018 (peralihan) dan September (banjir) 2018. Pengambilan sampel ikan dengan menggunakan jaring insang percobaan dengan ukuran mata jaring 1; 1,5; 2; 2,5 dan 3 inci yang dipasang pada 3 (tiga) stasiun pengamatan dan hasil tangkapan nelayan setempat. Komunitas ikan di Danau Pangelang tersusun atas 37 spesies dari 30 genera dan 12 famili. Pada musim surut terdapat 21 jenis ikan yang tertangkap, 17 jenis pada musim pancaroba, dan 16 jenis di musim banjir pada saat air surut. Umumnya jenis ikan yang tertangkap pada musim surut adalah ikan detritivora, sedangkan pada musim peralihan jenis ikan yang tertangkap dari jenis planktivora hingga ikan pemakan serangga, dan pada musim banjir jenis ikan yang tertangkap dari jenis ikan herbivora.